MM Sort algorithms (International Journal of Engineering and Computer Science, 2016)
Sorting is used for arranging a data either in ascending order or descending order. I have discussed here in these paper about new Algorithm to solve the problem of sorting. The Algorithm to solve problem of sorting is on reference of BUBBLE sort technique. The procedure to sort the element is extremely different